2021
DOI: 10.22435/mpk.v31i3.4472
|View full text |Cite
|
Sign up to set email alerts
|

Gambir (Uncaria gambir Roxb.) as A Potential Alternative Treatment for Hyperlipidemia

Abstract: Gambir (Uncaria gambir Roxb.) is a member of family of Rubiaceae. In Asia including Indonesia, extracts of gambir are empirically used daily to weed out. The high content of catechin flavonoids in gambir has a pharmacological effect in the treatment of hyperlipidemia that potential to be developed into traditional medicine. This literature review aimed to examine the potency of pharmacological effect of gambir as hyperlipidemia treatment therapy based on the results of studies in silico, in vitro, in vivo phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Atherosclerosis is a risk factor for coronary heart disease [ 122 , 123 ]. Several studies have shown that gambir can be used as an antihyperlipidemic [ 124 , 125 ]. Yunarto et al [ 126 ] used ethyl acetate extract from gambir leaves as an antihyperlipidemic in vivo.…”
Section: Uncaria Gambir Roxb Usesmentioning
confidence: 99%
“…Atherosclerosis is a risk factor for coronary heart disease [ 122 , 123 ]. Several studies have shown that gambir can be used as an antihyperlipidemic [ 124 , 125 ]. Yunarto et al [ 126 ] used ethyl acetate extract from gambir leaves as an antihyperlipidemic in vivo.…”
Section: Uncaria Gambir Roxb Usesmentioning
confidence: 99%
“…Uncaria gambir [18] The standardized extract in combination with Morus alba (1:1) was tested using carrageenan induced inflammation in mice…”
Section: Biological Activitymentioning
confidence: 99%
“…Uncaria gambir [18] Figure 7. Summarize of compounds, biological activities, and mechanism of biological activity of several Uncaria species in East Kalimantan Table 1 shows that the crude extract, fraction and isolated compounds from the 5 species of this genus in the East Borneo possess many biological properties, such as antioxidant, analgesic-antiinflamatory, cytoctoxic, antimicrobial, trombolytic, antidiabetic, anthelmintic and antihyperlipidemia with Uncaria gambir as the most frequently studied and published, especially in Indonesia and Malaysia, followed by Uncaria cordata and Uncaria tomentosa.…”
Section: Biological Activitymentioning
confidence: 99%
“…11 This plant has been known to possess pharmacological properties: it can be used as anti-inflammation, 12 antiseptic, 13 anticancer, 14 and anticholesterol. 15 Previous researches reported that phenolics in U. gambir extract such as catechin, quercetin, quinic acid have contributed to antioxidant activities. 16 Gambirin A1, A2, B1, B2 have also been isolated from methanol extract of U.gambir.…”
Section: Introductionmentioning
confidence: 99%